In vitro Selection of Drought Stress Tolerance in Rice (Oryza sativa L.) var. Jarava (Plant Tissue Culture and Biotechnology, 2019)
Abstract not availablePlant Tissue Cult. & Biotech. 29(1): 127-131, 2019 (June)